A rare cause of gastrointestinal bleeding, “GANT” - İpekçi, Fuat; Engin, Ömer; Çapkis, Yahya; Etit, Demet (Turkish Journal of Gastroenterology, 2014)
Abstract Acute gastrointestinal hemorrhage is frequently seen in emergency surgical conditions. Benign pathologies are generally responsible in etiologic factors. Our case is a GANT. GANT is a mesenchymal tumor originated from Cajal cells or precursors of them. Cajal cells are pacemaker cells in the intestinal wall. Because GANT is a very rare tumor, we would like to report our case to the medical literature. We think very rare cases and treatments of its as like our case create view point states in etiology of acute gastrointestinal hemorrhage.